Critique of Imperialism and War in Conrad’s Heart of Darkness and Coppola’s Apocalypse Now - et. al., Meera Krishnadas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Virginia Woolf, in her essay ‘Joseph Conrad’, wrote “If as novelist you wish to test man in all his relationships, the proper antagonist is man; his ordeal is in society, not solitude.” Conrad, through the semi autobiographical eyes of Marlow, who is released into a primitive society in the African interiors, questions the stereotyped cultural gap between the ‘civilized’ and the ‘barbaric’. He also explores the extremities of a coloniser with the character of Kurtz. Kurtz, a white man invading the cultural space of the native African tribe for his personal greed, goes mad as he gets sucked into its centre unable to escape. While exploring the seedy underbelly of imperialism the text challenges the permutability of cultures and its resistance to go hand in hand with each other. Through the process, Conrad also builds a background image of the native African tribe which, I argue, appears to be the pigeonholed projection of a white man’s perspective. Thus the objective of this paper is to look at how his critique of the white man’s burden towers above his, perhaps unintentional, but unfair portrayal of the black man’s image and culture.